The Impacts of Green Buildings on Energy Efficiency and Green Space in Kabul City: A Case Study of the Faculty of Environmental Sciences Building - Hashimi, Sayed Mohammad Tamim; Mangal, Mohammad Rafiq; Shirzad, Mohammad Dawood (Journal of Natural Sciences – Kabul University)
There are different methods for software development. One of them is the plan-based development method. The plan-based development method has different stages in which all the process activities are planned in advance. Another important method is called incremental development, incremental development is a modern method for project management that involves dividing a complex project into smaller and independent modules. In this article, the plan-based development method and the incremental development method are compared. In this research, a comparative and descriptive method are used and the expected results are as follows: In the plan-based development method, it depends on the knowledge of the customer and in the incremental method, it depends on the people in the team, making changes in the incremental method is cheap but, in the plan, -based development method it is expensive. Plan-based development requires a larger team, while the incremental method requires a smaller team.